SBP in the Context of Islamic Principles and Sharia Compliance: A Systematic Literature Review - Latifannisa, Nuri; Rahmi, Yuri; Afdal, Zul (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This analysis is based on previous research that focused more on Sharia operational aspects, such as Sharia-based financial products or the Islamic banking system, while the understanding of compliance with Sharia principles in various industry sectors to support Sustainable Business Performance (SBP) is still limited. This study aims to identify, review, and systematize previous research on the impact of compliance with Sharia principles on SBP. The methodology used is a Systematic Literature Review (SLR) with the PRISMA method with a period of 2020-2024. The results of the study show that compliance with Sharia principles has a significant impact on SBP. Sharia compliance provides an opportunity to build consumer trust, expand access to a wider market, and improve financial resilience and corporate stability, especially through more prudent risk management and the absence of adverse practices.